Electron Heating Scales in Collisionless Shocks Measured by MMS. Issue 5 (10th March 2023) - Johlander, Andreas; Khotyaintsev, Yuri V.; Dimmock, Andrew P.; Graham, Daniel B.; Lalti, Ahmad
Abstract: Electron heating at collisionless shocks in space is a combination of adiabatic heating due to large‐scale electric and magnetic fields and non‐adiabatic scattering by high‐frequency fluctuations. The scales at which heating happens hints to what physical processes are taking place. In this letter, we study electron heating scales with data from the Magnetospheric Multiscale (MMS) spacecraft at Earth's quasi‐perpendicular bow shock. We utilize the tight tetrahedron formation and high‐resolution plasma measurements of MMS to directly measure the electron temperature gradient. From this, we reconstruct the electron temperature profile inside the shock ramp and find that the electron temperature increase takes place on ion or sub‐ion scales. Further, we use Liouville mapping to investigate the electron distributions through the ramp to estimate the deHoffmann‐Teller potential and electric field. We find that electron heating is highly non‐adiabatic at the high‐Mach number shocks studied here. Plain Language Summary: Shock waves appear whenever a supersonic medium, such as a plasma, encounters an obstacle. The plasma, which consists of charged ions and free electrons, is heated by the shock wave through interactions with the electromagnetic fields. In this work, we investigate how electrons are heated at plasma shocks. A key parameter to electron heating is the thickness of the layer where the heating takes place. Here, we use observations from the four Magnetospheric Multiscale spacecraft that regularly cross the standing bow shock that forms when the supersonic plasma, known as the solar wind, encounters Earth's magnetic field. We find that the thickness of the shock is larger than previously reported and is on the scales where ion physics dominate. We also find that the electron heating deviates significantly from simple adiabatic heating. Key Points: Using multipoint data from Magnetospheric Multiscale, we find that electron heating takes place on ion scales in the quasi‐perpendicular shock ramp We show that the time series of the temperature does not represent the spatial profile due to varying shock ramp speed Electron distributions in the ramp and downstream of the shock show that electrons are heated non‐adiabatically